2021
DOI: 10.1186/s43042-021-00191-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased vitamin D levels in children with primary mono-symptomatic nocturnal enuresis

Abstract: Background Nocturnal enuresis (NE) is a common voiding problem in pediatric populations. Relatively, few studies have investigated the 25-Hydroxyvitamin D and NE associations in children, which may open up a new research area on the effect of vitamin D as nutritional therapy in the treatment of NE. The aim of this study was to determine the level of 25-hydroxyl vitamin D among children and adolescents with nocturnal enuresis in comparison to non-enuretic Egyptian children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…A study on 50 PMNE Egyptian children showed that vitamin D values were smaller in healthy non-bedwetting children. Vitamin D < 20 ng/mL was observed in 23 subjects (46%) in the enuretic group and only 8 children (16%) in the control group (20). In this study, vitamin D levels were divided into two categories (< 20 and > 20 ng/mL), and the relationship between vitamin D and the severity of bedwetting was not studied.…”
Section: Discussionmentioning
confidence: 86%
“…A study on 50 PMNE Egyptian children showed that vitamin D values were smaller in healthy non-bedwetting children. Vitamin D < 20 ng/mL was observed in 23 subjects (46%) in the enuretic group and only 8 children (16%) in the control group (20). In this study, vitamin D levels were divided into two categories (< 20 and > 20 ng/mL), and the relationship between vitamin D and the severity of bedwetting was not studied.…”
Section: Discussionmentioning
confidence: 86%
“…This cut-off was 13.7 ng/dl. Previous research has defined a higher cutoff value of 19 ng/dl, but this value was used to discriminate between enuretic and healthy children [ 11 ]. Therefore, it could be concluded that, with higher levels of vitamin D, the child’s chance of being enuretic decreases.…”
Section: Discussionmentioning
confidence: 99%
“…El-Baz et al. 2021 estimated that 46% of pediatric patients with primary nocturnal enuresis had low abnormal vitamin D levels [ 11 ].…”
Section: Methodsmentioning
confidence: 99%